Transfusion of red cells in hematopoietic stem cell transplantation (TRIST): study protocol for a randomized controlled trial - Tay, Jason; Tinmouth, Alan; Fergusson, Dean; Allan, David (Université d'Ottawa | University of Ottawa, 2011)
Abstract Background Insight regarding transfusion practices in Hematopoietic Stem cell Transplantation (HSCT) are lacking and the impact of red cell transfusion in this high risk group on outcomes following HSCT are not well appreciated. Red blood cell transfusion can be life-saving, however, liberal use of transfusion in critically ill patients failed to demonstrate significant clinical benefit. A large number of other observational studies have also demonstrated an association between red blood cell transfusions and increased morbidity such as infections and multi organ failure as well as increased mortality. The role of red cell transfusion on the clinical outcomes observed in patients undergoing HSCT remains poorly understood and a prospective randomized study of transfusion is required to gain insight and knowledge on best transfusion practices in this high risk population. Methods This report describes the design and methodological issues of a randomized pilot study evaluating red cell transfusion triggers in the setting of Hematopoietic Stem Cell Transplantation. This study has been funded by a peer review grant from the Canadian Blood Services and is registered on Clinicaltrials.gov NCT01237639. Results In 3 Canadian centres, 100 patients undergoing Hematopoietic Stem Cell Transplantation will be randomized to either a restrictive (target hemoglobin of 70-90 g/L) or liberal (target hemoglobin of 90-110 g/L) red cell transfusion strategy, based daily hemoglobin values up to 100 days post-transplant. The study will stratify participants by centre and type of transplant. The primary goal is to demonstrate study feasibility and we will collect clinical outcomes on 1) Transfusion Requirements, 2) Transplant Related Mortality, 3) Maximum grade of acute Graft versus Host Disease, 4) Veno-occlusive Disease, 5) Serious Infections, 6) Bearman Toxicity Score, 7) Bleeding, 8) Quality of Life, 9) Number of Hospitalizations and 10) Number of Intensive Care Unit (ICU) Admissions. Conclusion Upon completion, this pilot trial will provide preliminary insight into red cell transfusion practice and its influence in hematopoietic stem cell transplant outcomes. The results of this trial will inform the conduct of a larger study.